Palliative homecare patients’ emergency department visits near end of life: A retrospective homecare and emergency department chart review to determine characteristics and outcomes - Pooler, Charlotte; O’Dochartaigh, Domhnall; Mekechuk, Joy; Desrochers, Christa; Chamberlain, Stephanie; Spiers, Jude A. (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Meadowlight Media, 2026)
Background: Palliative patient visits to the emergency department (ED) may be necessary but also increase the likelihood of a hospital death. Risk factors for ED visits are reported in the literature. It is important to know more about characteristics of patients who go to the ED near end-of-life and their outcomes to determine strategies for care.Methods: A retrospective descriptive study of palliative homecare adults who had one or more ED visits in their last 6 weeks of life was conducted within a large western Canadian health region. Between April 1, 2016, to March 31, 2017, there were 1,033 known ED visits by the 1,874 palliative homecare patients. Random and purposeful sampling were conducted to determine a sample of 191 ED visits by acuity, geographical settings, and outcomes. Detailed chart reviews were conducted between January 15, 2019, and February 19, 2020, on homecare and hospital charts.Results: There were 191 ED visits reviewed by 170 unique patients within 6 weeks of death: 142 had a primary cancer diagnosis; 55.3% had more than one ED visit; 73.5% went to ED within 2 weeks before death. Forty patients had unusual outcomes: ED deaths, Intensive Care Unit admissions, and those who left ED. Most presented with a Canadian Triage and Accuity Scale (CTAS) rating of 1–3 (89.4%). The majority (63.5%) of primary concerns were pain, weakness/falls or dyspnea. Most patients had care that aligned with a palliative approach; however, most (88%) died in hospital although they indicated a preference for home or hospice death.Conclusions: Patients visited ED primarily for urgent symptom management. Emergency department visits were associated with high risk of in-hospital deaths. Opportunities were revealed for earlier identification and referral to palliative resources and collaboration across sectors, including populations with chronic end-stage organ disease.